PENERAPANMODEL MAKE A MATCH UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA SD NEGERI 008 PALEMBANG - Viyolia, Vera; Idris, Muhamad; Budi Irawan, David (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the uneven learning activity of fourth-grade students at SD Negeri 008 Palembang. This study aims to describe the implementation of the Make A Match learning model and to illustrate changes in students’ learning activity in the science and sosial studies lesson on the topic “Me and My Needs”. This research uses a qualitative approach with a descriptive method, employing data collection techniques through observation, interviews, and documentation. The results of the study show that the Make A Match learning model has been implemented according to the planned learning stages. The findings indicate that students actively engaged in finding card pairs, discussing, and presenting the results of their discussions. The more engaging learning process encourages students to participate more actively, ask questions, and answer questions. Overall, the implementation of the Make A Match model in IPAS lessons in the fourth grade at SD Negeri 008 Palembang has run well and supports students’ learning activity